COMPARATIVE ANALYSIS OF WASTE MANAGEMENT POLICY IMPLEMENTATION (A CASE STUDY BETWEEN PEKANBARU CITY AND PADANG CITY) - Vivin Delvya Roza; Harapan Tua RFS (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Waste management problems in Indonesia have become a crucial challenge, especially in major cities. This study aims to analyze the comparative implementation of waste management policies in Pekanbaru City and Padang City using the George C. Edward III policy implementation model. This qualitative research with a literature study approach analyzes four variables: communication, resources, bureaucratic structure, and disposition. The results show that Pekanbaru City faces significant constraints in all four variables, with a waste management achievement of 66.49% and even experiencing a waste emergency status in 2025. In contrast, Padang City achieved 94.02% and received various international awards. This difference is caused by more effective policy communication, massive community empowerment through 182 waste banks, strong fiscal commitment with a budget of Rp 70 billion, solid multi-stakeholder coordination, and a high implementer disposition in Padang City.